ZeaPackage: The potential of corn husk (Zea mays L.) for biodegradable paper bags as a strategy for waste reduction and implementation of circular economy concept - Azrial, Fahmi; Afrida, Febrian; Al-Mupidah, Olivia Jindani; Aulya, Rosya Diyaul (Journal of Agrosociology and Sustainability, 2025)
Background: Plastic waste has become a global issue, including in Indonesia, where its growing impact has prompted the need for sustainable alternatives. Corn husk, an abundant agricultural waste in Indonesia, presents a potential raw material for producing biodegradable paper bags, aligning with circular economy principles and addressing the increasing demand for eco-friendly packaging. Method: This study uses a comprehensive literature review, drawing from scientific journals, textbooks, and official publications. Data analysis is conducted through descriptive and comparative techniques, including SWOT analysis, to assess the viability of corn husk-based biodegradable paper bags as an alternative to plastic. Findings: The study reveals that ZeaPackage, a biodegradable paper bag made from corn husks, is a promising alternative to plastic bags. Corn husks' high cellulose content and abundance make them ideal for large-scale production, offering an eco-friendly solution while supporting circular economy goals. Conclusion: ZeaPackage has significant potential as an environmentally sustainable alternative to plastic bags. By leveraging the abundant supply of corn husks, it contributes to waste reduction and aligns with circular economy principles, though challenges in implementation remain. Novelty/Originality of this article: This study highlights the innovative use of corn husk as a raw material for biodegradable packaging, offering a practical solution to plastic waste while adding value to agricultural by-products in Indonesia.